Twenty-four-hour time dependency of clopidogrel effects in patients with acute coronary syndromes: The CiCAD-Study. (19th May 2019) - Gruber, Susanne Claudia; Freynhofer, Matthias Karl; Willheim, Martin; Weiss, Thomas Werner; Egger, Florian; Hübl, Wolfgang; Huber, Kurt
Abstract: Long-term evidence shows an increased risk of cardiovascular events in the morning hours and recent studies in aspirin-treated patients have shown increased platelet reactivity at the end of the dosing interval. Similar pharmacodynamic analyses of adenosine-diphosphate (ADP) receptor inhibitors are scarce. We therefore investigated changes in clopidogrel-dependent platelet function and activation over 24 h and whether enhanced platelet turnover might explain diurnal variability of platelet function and activation. Twenty-one patients after acute coronary syndromes (ACS) on maintenance doses of clopidogrel (75 mg) and aspirin (100 mg) Once per day (OD) were included. Blood was collected at five time points in 24 h. Platelet function and activation was analyzed by vasodilator-stimulated phosphoprotein-phosphorylation (VASP-P), Verify Now, multiple electrode aggregometry (MEA), and platelet PAC-1 and P-selectin (P-sel) expression. Additionally, platelet count, mean platelet volume (MPV), and reticulated platelet fraction (RPF) were analyzed. There was significant diurnal variability of clopidogrel effects as documented with VASP-P, Verify Now, and PAC-1 and P-sel (all p < 0.05), whereas MEA did not differ over 24 h. Neither MPV nor RPF varied significantly over 24 h. In patients with high RPF, platelet function and activation was significantly higher in all assays, compared to patients with low RPF (all p < 0.05). However, the changes over time in low versus high RPF groups were similar. ADP-dependent platelet function and activation recovers significantly at the end of the 24-h dosing interval in patients with ACS on a maintenance dose of clopidogrel and aspirin. Although platelet function and activation is increased in patients with higher RPF, platelet turnover might not explain the observed diurnal variability.